PENGARUH METODE LATIHAN POWER OTOT TUNGKAI TERHADAP HASIL LOMPAT JAUH GAYA JONGKOK PADA PESERTA DIDIK PUTRA KELAS XI MAN 2 KAMPAR - Nelsi Hayanti (Sport Pedagogy Journal, 2022)
The  purpose  of  the study. The purpose of this study was to determine the effect of the leg muscle power training method on the squat style long jump in male students. The training method used is an experimental research method with the research design that the author uses in this study is one group pretest and posttest..Materials and methods.. The sample in this study used purposive sampling technique. The tests and measurements of this research were carried out by male students of MAN 2 Kampar with a total sample of 16 students. To get the results of the long jump squat style, taking the pre-test and post-test scores is to do the long jump 2 times and the farthest jump range is taken as the final value.Results. The results of the study based on the statistical output of "test statistics", obtained the value of t-count (6,630) (1,753) and Asymp.Sig (2-tailed) with a value of 0.000.Conclusions. The results of the study based on the statistical output of "test statistics", obtained the value of t-count (6,630) (1,753) and Asymp.Sig (2-tailed) with a value of 0.000. Because the value of 0.000 is smaller than 0.05. This means Ha: accepted and Ho: rejected. With a percentage increase of 1.1125%. So it can be concluded that "there is a significant difference between the pre test scores and the post test scores".